2022
DOI: 10.1007/s00382-022-06598-2
|View full text |Cite
|
Sign up to set email alerts
|

Extreme indices of temperature and precipitation in South America: trends and intercomparison of regional climate models

Abstract: Regional Climate Models (RCMs) provide climate information required for the evaluation of vulnerability, impacts, and adaptation at ner scales than their global driving models. As they explicitly resolve the basic conservation and state equations, they solve physics with more detail, conserving teleconnection of larger scales provided by GCMs. In South America (SA), the regional simulations have been historically evaluated principally on climatological aspects, but the representativeness of extremes still need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…The regions considered were the Pampas region (R1), northeast Argentina (R2), central Argentina (R3), northwest Argentina (R4) and Argentinian Patagonia (R5) (Fig. 1) following Balmaceda-Huarte and Bettolli (2022).…”
Section: Station Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The regions considered were the Pampas region (R1), northeast Argentina (R2), central Argentina (R3), northwest Argentina (R4) and Argentinian Patagonia (R5) (Fig. 1) following Balmaceda-Huarte and Bettolli (2022).…”
Section: Station Datamentioning
confidence: 99%
“…Whereas statistical downscaling of daily maximum and minimum temperatures (Tx and Tn, respectively) has been evaluated in a previous work by Balmaceda-Huarte and Bettolli (2022), where a set of analogs, generalised linear models and arti cial neural networks were employed. The authors found, during an observed period using a cross-validation approach, a good performance of the models, being successful to reproduce the mean values, extreme percentiles and temporal variability from seasonal to interannual.…”
Section: Introductionmentioning
confidence: 99%
“…The rectangles illustrated in Figure 1 indicate the subdomains selected (Table 1) to analyze hydrological drought events on the continent. We considered subdomain 8 (Patagonia) because, in this region, the Andes have a lower height, while we did not perform analysis for the other parts of the Cordillera due to uncertainties in the reference data [97]. The rectangles illustrated in Figure 1 indicate the subdomains selected (Table 1) to analyze hydrological drought events on the continent.…”
Section: Study Areamentioning
confidence: 99%
“…For this, daily data from 1995 to 2014 were used, with 0.5 • horizontal resolution-available online: https://ftp.cpc.ncep.noaa.gov/precip/CPC_UNI_PRCP/ GAUGE_GLB/RT/ (accessed on 25 January 2022). CPC data proved adept at representing average and seasonal precipitation patterns over most of SA [93] but presented uncertainties in regions of complex topography, such as the Andes Mountains [97].…”
Section: Reference Datasetmentioning
confidence: 99%
“…These indices provide a framework for defining and assessing changes in the Earth's climate system (URL: http://etccdi.pacificclimate.org/list_27_indices.shtml ). These statistically reliable indices are designed to capture crucial characteristics such as the frequency, intensity, and duration of daily temperature and precipitation extremes 26 , 40 44 . However, research focusing on daily precipitation and temperature in the NEI region has been limited, with only a few studies conducted in the past decade.…”
Section: Introductionmentioning
confidence: 99%